CHARACTERISTICS OF RETINAL DETACHMENT PATIENTS WITH PROLIFERATIVE VITREORETINOPATHY AT Dr. SOETOMO GENERAL ACADEMIC HOSPITAL - Ifan Romadhon Lukmana; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (Indonesian Vitreoretinal Society, 2019)
Introduction: The aim of this study is to evaluate the incidence and characteristics of retinal detachment patients with proliferative vitreoretinopathy. Methods: Retrospective review of medical record from primary retinal detachment (RD) patients with proliferative vitreoretinopathy (PVR) between 2013 and 2017 at Outpatient Department of Ophthalmology, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Result: : The number of RD patients with PVR at Dr. Soetomo General Academic Hospital in 2013-2017 was 80 patients (21%), consisting of 59 men and 21 women with mean of age was 47.5 ± 14.3 years. The characteristics of the subjects were phakic 72.5%, aphakic 1.25%, high myopia 23.75%, history of trauma 18.75% and affected to right eye 60%. Retinal characteristics were break conditions in the retina (located at superotemporal (34%), horseshoe tear (56%), and single break (60%)), macula off (90%), area of detachments were 4 quadrants (43,75%), PVR conditions were grade B PVR (45%), mean duration of RD was 156 days, mean length of surgery waiting list was 61.1 days. The majority of treatment types were vitrectomy (70,4%), majority of tamponade using silicone oil (59.3%), majority of pre-operative and post-operative visual acuity were less than 3 meters counting finger, pre-operative (91.25%) , post-operative 1 month (76%) and 6 months (52.5%), and the majority of post-operative retinal reattachment were 77.3%. Conclusion: The results of this study indicate the number of RD patients with PVR was lower than previous studies. Various results of patient characteristics can be used as guidelines for ophthalmologists in determining actions and explaining the prognosis of the disease. Further research with a larger sample size and prospective methods will be better able to provide better results. Keywords: retinal detachment, proliferative vitreoretinopathy, characteristic pvr